Moleque Estranho: a trajetória de um corpo artista - MENEZES, Jean Victor Rocha de (2023)
Writing about an individual’s trajectory with all its peculiarities, according to Gilles Deleuze and Felix Guattari’s rhizome theory. Reliving events in a black, peripheral individual’s life and how those events made him the man he is nowadays. Narrating the life story through many art forms, like poems to narrate the main points of its rhizome. Then, creating a scenic experiment using Animated Forms Theatre to make a final scene of his trajectory.